2023
DOI: 10.3390/metabo13020234
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomic Signature of Obesity and Risk of Colorectal Cancer: Two Nested Case–Control Studies

Abstract: Obesity is a leading contributor to colorectal cancer (CRC) risk, but the metabolic mechanisms linking obesity to CRC are not fully understood. We leveraged untargeted metabolomics data from two 1:1 matched, nested case–control studies for CRC, including 223 pairs from the US Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial and 190 pairs from a prospective Chinese cohort. We explored serum metabolites related to body mass index (BMI), constructed a metabolomic signature of obesity, and exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The circulating metabolome is associated with cancer risk [ 5 , 8 , 9 ]. Germline mutations in DNA repair genes elevate cancer risk by imposing a high mutation load on fast-proliferating epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The circulating metabolome is associated with cancer risk [ 5 , 8 , 9 ]. Germline mutations in DNA repair genes elevate cancer risk by imposing a high mutation load on fast-proliferating epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating metabolome reflects whole-body metabolic processes, which are influenced by genes, lifestyle factors, and health status [ 4 7 ]. Based on findings that adiposity-linked circulating metabolite signature is associated with elevated CRC risk [ 8 ], while a metabolite profile reflecting a healthy lifestyle is associated with lower CRC risk [ 5 , 9 ] circulating metabolome holds the potential for characterizing a phenotype susceptible to CRC development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported the association between obesity and CRC (Mandic et al, 2023;Yang et al, 2023;Ye et al, 2020). SQLE, which is the first oxygen-requiring enzyme involved in cholesterol biosynthesis, is upregulated during hypoxic conditions in premalignant formation (Coates et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In studies to date, adiposity signatures were not shown to substantially mediate the obesitycancer associations for advanced prostate cancer 167 or breast cancer 168 . There was 12% mediation for endometrial cancer 169 and results were mixed for colorectal cancer 169,170 . This relative lack of mediation, when compared with studies of "classical mediators", may reflect low statistical power or that adiposity signatures are not sufficiently specific measures of the key metabolites.…”
Section: "Omics"-identified Biologic Factorsmentioning
confidence: 95%